Intrinsic or Extrinsic Motivation: Which More Dominant at Excellent Class in Indonesia Middle School Students? - Hasanudin, Hasanudin; Woretma, Inna Mahjanisuri; Maghfiroh, Nella U.; Wael, Ahmad (JULIET: Journal of English Language and Literature, 2024)
This study aims to measure middle school students' dominant motivation in learning English at an excellent class and the interference of extrinsic motivation toward intrinsic motivation. A survey was used on thirty-one excellent class students. The results showed students' intrinsic motivation is more central than their extrinsic motivation, which the students felt self-desire and satisfaction are the central aspect affecting their motivation in learning English. Moreover, the scores of extrinsic motivation revealed that prizes and imitating something are the essential part of increasing students' motivation. Likewise, the average motivation results found that students' extrinsic motivation comparatively dominance with their intrinsic motivation.